Social networking sites for online mentoring and creativity enhancement - Radzuwan, Ab Rashid; Mohd Fazry, A. Rahman (2014)
The main purpose of this study is to investigate whether social networking sites SNS, especially Facebook, could be used to enhance interior design students' creativity by connecting them with professional interior architects in an online mentoring activity. Of particular interest is to explore the perceptions of the students and the interior architects regarding the use of SNS in fostering collaboration between learners and professionals. The study involved five professional interior architects and ten interior design students in a community college in Malaysia. This study employed a one group pre-test and post-test experimental design. Triangulation, involving semi-structured interviews, was used. The findings show that engagement in an online mentoring activity with professional interior architects via Facebook does contribute to the enhancement of creativity among the students. The use of SNS in fostering collaboration between learners and professionals is also perceived positively by both the students and interior architects.